Biallelic Variants in LAMB1 Causing Hydranencephaly: A Severe Phenotype of a Rare Malformative Encephalopathy - Sen, Kuntal; Kaur, Shagun; Stockton, David W.; Nyhuis, Mary; Roberson, Jacquelyn (American Journal of Perinatology Reports, 2021)
Case Report A 32-year-old female with a history of three prior pregnancy losses presented for genetic testing following an ultrasonography diagnosis of fetal hydranencephaly. Baby was born via C-section and was noted to have a head circumference of 48 cm, in addition to ocular and cardiac anomalies and dysmorphic features. Whole genome sequencing revealed a homozygous variant in LAMB1 gene.Discussion The pathobiogenesis of hydranencephaly is incompletely understood and is attributed to vascular, infectious, or genetic etiology. Herein we present LAMB1 as a monogenic cause of fetal hydranencephaly which was incompatible with life. Previously, LAMB1-associated phenotype consisted of cobblestone lissencephaly and hydrocephalus, developmental delay, and seizures. Our proband expands the phenotypic spectrum of this malformative encephalopathy.
Keywords: hydranencephaly; LAMB1; α-dystroglycanopathy; whole genome sequencing